2018
DOI: 10.1038/s41598-018-27438-6
|View full text |Cite
|
Sign up to set email alerts
|

MiR-744-5p inducing cell death by directly targeting HNRNPC and NFIX in ovarian cancer cells

Abstract: MicroRNAs (miRNAs) play an important role in the regulation of gene expression. The binding to target messenger RNAs (mRNAs) results in mRNA cleavage or inhibition of the translational machinery leading to decreased protein levels. Various signalling pathways, including apoptosis are modulated by miRNAs. Here, we investigated the role of miR-744-5p in apoptosis signalling in ovarian cancer cell lines. MiR-744-5p expression was reduced in the cancer cell lines independent of the host gene MAP2K4. Overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 54 publications
4
87
0
Order By: Relevance
“…A qRT-PCR based study has also reported reduced expression of miR-423 in CLL patients particularly in the context of higher lactate dehydrogenase (LDH) activity 29 . Higher expression of miR-744 among older female patients with ovarian carcinoma has been reported to correlate with prolonged disease free survival, suggesting its protective influence 39 . This is comparable to findings in this study where higher expression of miR-744 correlates with extended time to first treatment in CLL patients as compared to those with reduced expression.…”
Section: Sr Nomentioning
confidence: 99%
“…A qRT-PCR based study has also reported reduced expression of miR-423 in CLL patients particularly in the context of higher lactate dehydrogenase (LDH) activity 29 . Higher expression of miR-744 among older female patients with ovarian carcinoma has been reported to correlate with prolonged disease free survival, suggesting its protective influence 39 . This is comparable to findings in this study where higher expression of miR-744 correlates with extended time to first treatment in CLL patients as compared to those with reduced expression.…”
Section: Sr Nomentioning
confidence: 99%
“…Interestingly, miR‐744 seems to mediate ambivalent effects depending on respective cancer tissue. Thus, proapoptotic impact was reported repeatedly, whereas others observed proproliferative properties of miR‐744 on cancer cells . Nevertheless, the clonal variability of CHO production cells frequently observed after generating clonal cell lines may also be considered and therefore a larger number of deletion and control clones should be analyzed to undermine observed functional improvements .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we applied the CRISPR/Cas9 system for a rapid and straightforward CHO cell line engineering approach by knocking out miR‐744 from the CHO cell genome in order to modify production‐relevant cellular functions. MiR‐744 is predominantly studied in various human tumors where it has been demonstrated to influence cell proliferation and apoptosis . While a large high‐throughput miRNA screen demonstrated the tremendous potential of miRNA overexpression as an opportunity to enhance CHO cell performance, we here exploited this knowledge to improve the productivity of monoclonal antibody (mAb) producing CHO cells by deleting miR‐744 activity in a recombinant mAb‐producing CHO cell line.…”
Section: Introductionmentioning
confidence: 99%
“…18 MiR-744-5p induces cell death of ovarian cancer cells via targeting HNRNPC and NFIX. 19 Nonetheless, this was the first time to investigate the link between HNRNPC and LEF1-AS1 in OS cells. Our analysis displayed that LEF1-AS1 could bind to HNRNPC.…”
Section: The Expression Of Lef1-as1 and Lef1 Is Upregulated In Ostementioning
confidence: 99%